Premorbid academic and social functioning in patients with schizophrenia and its associations with negative symptoms and cognition. (8th July 2018) - Bucci, P.; Galderisi, S.; Mucci, A.; Rossi, A.; Rocca, P.; Bertolino, A.; Aguglia, E.; Amore, M.; Andriola, I.; Bellomo, A.; Biondi, M.; Cuomo, A.; et al.
Abstract : Objective: The study aimed to explore premorbid academic and social functioning in patients with schizophrenia, and its associations with the severity of negative symptoms and neurocognitive impairment. Method: Premorbid adjustment (PA) in patients with schizophrenia was compared to early adjustment in unaffected first‐degree relatives and healthy controls. Its associations with psychopathology, cognition, and real‐life functioning were investigated. The associations of PA with primary negative symptoms and their two factors were explored. Results: We found an impairment of academic and social PA in patients ( P ≤ 0.000001) and an impairment of academic aspects of early adjustment in relatives ( P ≤ 0.01). Patients with poor PA showed greater severity of negative symptoms (limited to avolition after excluding the effect of depression/parkinsonism), working memory, social cognition, and real‐life functioning ( P ≤ 0.01 to ≤0.000001). Worse academic and social PA were associated with greater severity of psychopathology, cognitive impairment, and real‐life functioning impairment ( P ≤ 0.000001). Regression analyses showed that worse PA in the academic domain was mainly associated to the impairment of working memory, whereas worse PA in the social domain to avolition ( P ≤ 0.000001). Conclusion: Our findings suggest that poor early adjustment may represent a marker of vulnerability to schizophrenia and highlight the need for preventive/early interventions based on psychosocial and/or cognitive programs.